SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BERAS UNTUK KELUARGA MISKIN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING DI KANTOR KEPALA DESA GUMPANG - Deka Agus Astika; Didik Nugroho; Tri Irawati (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2018)
The Gumpang Village Head Office is one of the village government offices that provide both economic and social services. In the service of the village head, there is a social program that every month there is a program for poor families, which is included in certain criteria governed by the rule of government in the village head gumpang. The all citizens are entitled to get Raskin, but only for those who belong to the poor family scope and food insecurity to support his family. For that in determining the poor family (based on criteria such as Earnings, Dependence Children, Home Conditions. Raskin program is only devoted to the poor citizens only. So as the village head is obliged to be able to select or select its citizens, to determine as the poor recipients of Raskin. Because the condition of the society is so diverse and the status of different citizens and there are various upheavals between the poor and the poor, where the citizens in the village of gumpang that look poor not necessarily poor and the citizens who look rich not necessarily rich, because citizens changed from rich to poor, poor to rich, making it difficult for village heads to determine poor families as Raskin recipients. Solution to handle the problem is to make Decision Support System used method SAW (Simple Additive Weighting). This method is chosen because this method is capable for the ranking process which will select the best alternative from a number of alternatives (poor people) The technique used in this research is with Observation, Interview and literature study The design of this system is made with Context Diagram, HIPO, DAD, inter-table relation and database design. Applications are created using PHP programming languages and databases using My SQL. The old system analysis to calculate the error rate of the old system has an error rate of 1 that is the result difference between the new system with the old system is 1 riping so that the accuracy of the new system is 90%. The system has been made capable of determining the poor based on many criteria resulting in more precise and comprehensive resultsKeywords: Raskin, Population, SAW, Decision Support System